If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 52 + -4x = 5x + 24 Reorder the terms: 52 + -4x = 24 + 5x Solving 52 + -4x = 24 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 52 + -4x + -5x = 24 + 5x + -5x Combine like terms: -4x + -5x = -9x 52 + -9x = 24 + 5x + -5x Combine like terms: 5x + -5x = 0 52 + -9x = 24 + 0 52 + -9x = 24 Add '-52' to each side of the equation. 52 + -52 + -9x = 24 + -52 Combine like terms: 52 + -52 = 0 0 + -9x = 24 + -52 -9x = 24 + -52 Combine like terms: 24 + -52 = -28 -9x = -28 Divide each side by '-9'. x = 3.111111111 Simplifying x = 3.111111111
| 16c=12+24c | | 3g-1=23 | | (x-12)+(16-2*x)=14 | | x*x+x+6=0 | | 2p+7q=46 | | 20yx=10-5yx | | 5y-11y= | | (x-12)+(16-2x)= | | 15yx=5-10yx | | -12(x-12)=-9(1+7) | | 5x+5=7+x | | 10x-17y= | | 13b=7-16b | | 3(w-2)=11 | | 2F=18 | | -16x=2-4x | | (4x+12)-8=(12+3x)-8 | | 9x+6y+2=0 | | 3(2q-7)-(3q-8)=22 | | 4x^2-27x+23=-4x+8 | | x+(x+4)=3+(x+1) | | 6x+14=23-3x | | 10x=51-7x | | -14x=7-9x | | x^2-9x-3=-8x-1 | | 3x+4=58-3x | | x^2+4x-28=4 | | 3x+9=79-7x | | -14x=7-9 | | Damn=you | | 10x=90-5x | | 4(3w+5)-30=7w |